Evaluation of the quality and accuracy of breast cancer knowledge among persian language websites - Sadaf Alipour; Shekoofeh Nikooei; Reza Hosseinpour; Mohammad Javad Yavari Barhaghtalab (BMC, 2022)
Abstract Introduction The internet has become a powerful worldwide information source that revolutionized access to knowledge, especially in the fields of health and medicine (health knowledge). Therefore, providing high-quality, accurate, reliable, and relevant information on dependable websites is a possible way of providing the patient with needed information and, thus, achieving the benefits of informed patients regarding outcomes. This study aimed to evaluate the quality and accuracy of breast cancer knowledge among Persian language websites. Methods Two search engines were searched in the Persian language about breast cancer. The first 30 websites were selected for further evaluation based on the completeness, correctness, transparency, and accessibility of health knowledge. The DISCERN instrument was used to assess the quality of the Persian language websites on this issue. Results Among the 30 websites, about 23% of websites provide completely correct information and about 30% provide mostly correct information. Sixty percent of the websites provided author information, and 46% of them had a healthcare professional or expert as the author. Sixty percent of the websites stated the creation date on the pages, while 40% of them did not provide any health knowledge. Scores on accessibility were always easy for most of the websites. Based on the quality rating system of DISCERN, about 60% of the websites were presented as very poor. Conclusion Website rankings enable healthcare professionals to identify and signpost patients to reliable up-to-date websites to ensure that patients receive high-quality knowledge. This review has provided evidence of inadequate and inaccurate health knowledge about breast cancer on the Persian language websites. This issue requires further investigation to understand the barriers and solutions available to provide reliable information about breast cancer and how this information affects the patient's outcomes. Trial registration The project was found to be in accordance with the ethical principles and the national norms and standards for conducting research in Iran with the approval ID and date of IR.TUMS.IKHC.REC.1399.379 and 2021-01-01 respectively, and is registered with research project number 49890 in the Vice Chancellor for Research and Technology Development of Tehran University of Medical Sciences, Tehran, Iran. URL: https://ethics.research.ac.ir/EthicsProposalViewEn.php?id=170978 .